Effect of netting on Cryptophlebia leucotreta granulovirus for the management of Thaumatotibia leucotreta in South Africa - Luphondo, Kurhula Califonia (Rhodes University, 2026)
Baculoviruses constitute a diverse group of insect viruses that serve as natural pathogens and biocontrol agents, playing a vital role in regulating insect populations and providing a potential alternative to chemical pesticides. Thaumatotibia leucotreta, commonly known as false codling moth (FCM), is a significant citrus pest in South Africa. Native to sub-Saharan Africa, this pest poses a serious threat to exports due to strict zero-tolerance policies by certain markets for larvae in shipments, making effective control essential. Betabaculovirus cryleucotretae, Cryptophlebia leucotreta granulovirus (CrleGV), is an integral part of the systems approach used to manage T. leucotreta. Currently, four commercially available biopesticides, namely Cryptogran®, CryptoMax, Cryptex®, and Gratham, utilise CrleGV as their active ingredient. While these biopesticides have been successfully used for years, a major limitation of baculoviruses is their sensitivity to UV radiation, which renders them inactive within hours or days. Consequently, developing new control measures or enhancing existing methods is crucial to improving their persistence in the field. Shade nets are increasingly being adopted in South African citrus farming for multiple purposes, including protecting fruit from hail, sunburn, and wind. However, despite their widespread use, limited data are available on their impact on biotic factors, particularly entomopathogens. This study aimed to assess the impact of shade netting on CrleGV efficacy. The virus was propagated in T. leucotreta third and fourth instars to produce two separate stocks, which were used in experiments conducted at different times. Occlusion bodies (OBs) from larval cadavers were purified using the glycerol gradient method for the first stock (CrleGV-1) and a crude extraction method for the second stock (CrleGV-2). The concentrations of the virus stocks were determined through OB quantification using darkfield microscopy and a counting chamber, yielding values of 8.13 × 10¹⁰ and 2.69 × 10¹¹ OBs/ml for CrleGV-1 and CrleGV-2, respectively. To assess the effectiveness of CrleGV, semi-field exposure trials were conducted under netted and non-netted conditions using virus-treated fruit. The virus was exposed to natural UV radiation for different durations, 1, 7, 14, and 21 days in the first experiment, and 1, 3, 5, and 7 days in the second. After exposure, the virus was washed from the fruit, enumerated, and subjected to surface-dose bioassays to evaluate its virulence and persistence and, as such, provide insights into the level of UV protection that netted orchards offer for CrleGV-SA. Statistical analysis indicated that netting provided little protection to CrleGV against UV radiation in Experiment 1. However, the virus lost activity very quickly which resulted in low and inconsistent mortality of T. leucotreta neonates in surface dose bioassays. The highest average mortality recorded during this experiment was 58.33% and this was recorded under the netted treatment. To be able to make a better conclusion on the extent of protection shade nets provide to CrleGV, the second experiment was conducted. The results for this experiment confirmed those of Experiment 1, showing that CrleGV persisted longer under netting. The mortality recorded on bioassays conducted using the virus recovered from netted structures was consistently higher than that recorded from virus recovered from unnetted structures. Lethal concentrations, LC50 values, were also calculated. These were generally lower for the netted treatment than the unnetted. The findings obtained in this study demonstrate the potential for improving the persistence of CrleGV in managing T. leucotreta in citrus. As the first study to examine the influence of shade netting on CrleGV against T. leucotreta, it lays the groundwork for future research to explore the effects of netting on entomopathogens for improved management of T. leucotreta and other pests.
Keywords: Uncatalogued